ZNF32 induces anoikis resistance through maintaining redox homeostasis and activating Src/FAK signaling in hepatocellular carcinoma. (1st February 2019) - Li, Kai; Zhao, Gang; Ao, Jie; Gong, Di; Zhang, Jie; Chen, Yue; Li, Jun; Huang, Lugang; Xiang, Rong; Hu, Jiankun; Lin, Ping; Wei, Yuquan
Abstract: Tumor cells need to attain anoikis resistance to survive prior to metastasis making it a vital trait of malignancy. The molecular mechanism by which hepatocellular carcinoma (HCC) cells resist anoikis remains not fully understood. Here, we report that ZNF32 expression is markedly upregulated in HCC cells upon detachment. Enforced ZNF32 expression significantly promotes the anchorage-independent growth capability of HepG2 and Huh7 cells, whereas knockdown of ZNF32 results in increased apoptosis of HCC cells after detachment. Mechanistically, we demonstrate that ZNF32 overexpression suppresses the reactive oxygen species (ROS) accumulation and maintains mitochondrial membrane potential, leading to ATP, GSH and NADPH elevation and promoting HCC cell survival in response to suspension. Moreover, ZNF32 enhances the phosphorylation and activation of Src/FAK signaling. Src and FAK inhibitors effectively reverse ZNF32-induced anoikis resistance in HCC cells. Collectively, our findings not only reveal a novel and important mechanism by which ZNF32 contributes to anoikis resistance through maintaining redox homeostasis and activating Src/FAK signaling, but also suggest the potential therapeutic value of ZNF32 in HCC patients. Highlights: ZNF32 facilitates the anoikis resistance of HCC cells in vitro and in vivo. ZNF32 expression is regulated by intracellular ROS levels upon detachment. ZNF32 inhibits excess ROS accumulation and maintaining redox homeostasis in detached HCC cells. Antioxidants rescue ZNF32 deficiency-induced anoikis in HCC cells following detachment. Src/FAK signaling is required for ZNF32-mediated anoikis resistance.